2022
DOI: 10.54386/jam.v24i2.1631
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of maize (Zea mays L.) productivity using CERES-maize model in South Alluvial Plain Zone of Bihar, India

Abstract: Maize (Zea mays L.) is cultivated widely throughout the world and has the highest production of all the cereals. Worldwide, production of maize was more than 844.36 MT (FAO, 2017) and productivity of 5.22 t ha -1 . It is an important staple food in many countries and also used as animal feed and has many industrial applications. Owing to its tremendous genetic variability, the maize crop thrives well in a wide range of environments from tropical to temperate climate (Anon., 2014). Maize is grown in climates ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…This implies that de-crystallization of the clay during acid treatment occurred which is a confirmation of the interaction of the acids with the clay surface (Novakovic et al, 2008). Decline in intensity has previously been reported to be greatly influenced by the strength of the acid (Kumar et al, 2013) and this was also the case in this study as the trend was found to be SK > NK > PK ~ OK > AK.…”
Section: A Characterization Of Raw and Modified Adsorbents 1) Results...supporting
confidence: 85%
See 1 more Smart Citation
“…This implies that de-crystallization of the clay during acid treatment occurred which is a confirmation of the interaction of the acids with the clay surface (Novakovic et al, 2008). Decline in intensity has previously been reported to be greatly influenced by the strength of the acid (Kumar et al, 2013) and this was also the case in this study as the trend was found to be SK > NK > PK ~ OK > AK.…”
Section: A Characterization Of Raw and Modified Adsorbents 1) Results...supporting
confidence: 85%
“…All these allowed more surface creation in most of the acid-activated forms. Reports of the enhancement of surface areas of clay minerals through acid activation have been documented in literature (Kumar et al, 2013, Alvarez, et al 2017, Dim et al, 2021and Malima et al, 2021.…”
Section: ) Bet Analysis Resultsmentioning
confidence: 99%
“…Panax notoginseng PnbHLH1 TF positively regulates the synthesis of triterpenoid saponins (Zhang et al, 2017). Previous studies have shown that TF family members such as MYB (Li and Lu, 2014;Hao et al, 2020), WRKY (Ma et al, 2009;Singh et al, 2017a) and bHLH (Mertens et al, 2016;Jiang et al, 2021) are involved in the regulation of various secondary metabolites in plants; therefore, the TFs identified in this study that were upregulated in P. cyrtonema need to be further investigated.…”
Section: Discussionmentioning
confidence: 83%
“…The genomes of A.hypochondriacus (GCA_00753965.2; LAI score: 12.81), A. tuberculatus (Genome ID: 54057; LAI score: 6.72), A. hybridus (Genome ID: 57429; LAI score: 9.56), A. palmeri (GCA_025765695.1; LAI score: 4.99), and A. cruentus (GCA_019425755.1; LAI score: 14.42), respectively. input to the microsatellite identification tool Krait v1.3.3 (https:// github.com/lmdu/krait) (Du et al, 2017) to identify SSR markers using the parameters: mono-nucleotide repeats were not considered; the minimum number of repeats allowed for the di-nucleotide were six repeats; and for tri-nucleotide to hexanucleotide, five repeats (Paliwal et al, 2016;Singh et al, 2022). The maximum difference between the two SSRs is 100 bp.…”
Section: Sequence Data Retrievalmentioning
confidence: 99%